Análise comparativa das relações entre ensino e aprendizagem por professores e alunos - Osti, Andréia [UNESP] (2013)
In this research we identified and compared the representations of teachers and students on teaching and learning. The objective was to determine which aspects of these representations correspond to subjects and if they differ between students with high and low academic performance. Data collection was organized through a semi-structured interview. The study included twenty teachers and forty students in the 5th year of elementary school municipal public metropolitan region of Campinas. The responses from the interviews were categorized and analyzed by using the Fisher exact test, chi-square and Proportions. The results show that teachers and students present a partial view of the factors involved in teaching and learning. The learning process is understood as an individual and social factor. Teachers and students with high performance positively represent the environment of the classroom, unlike the students with lower academic performance.